Burden of rotavirus gastroenteritis in children <5 years of age in Greece: hospital-based prospective surveillance (2008–2010). Issue 12 (11th December 2013) - Konstantopoulos, Andreas; Tragiannidis, Athanasios; Fouzas, Sotirios; Kavaliotis, Ioannis; Tsiatsou, Olga; Michailidou, Elisa; Spanaki, Ariana; Mantagos, Stefanos; Kafetzis, Dimitris; Papaevangelou, Vana; Gopala, Kusuma; Holl, Katsiaryna
Abstract : Objectives: This study describes the epidemiology of rotavirus (RV) gastroenteritis (GE) disease following the introduction of RV vaccination in Greece in 2006. Design: A prospective hospital-based surveillance. Setting: A multicentre study was conducted at six hospitals in Greece between July 2008 and March 2010. The hospitals selected served 70% of the paediatric population in Greece. Participants: Children aged <5 years who visited the emergency rooms (ERs) or hospitalised with acute GE or acquired acute GE 48 h after hospitalisation and with a confirmed RV-positive stool test were enrolled. Primary and secondary outcome measures: The occurrence of RVGE among all acute GE ER visits and hospitalisations and the occurrence of nosocomial RVGE are reported with 95% exact CI. Age-specific proportions of RVGE, seasonality and prevalence of RV genotypes were estimated. Incidence rates of nosocomial acute GE and RVGE are expressed in terms of 1000 children-years with 95% exact Poisson CI. Median duration of hospitalisation and prolongation of hospitalisation due to nosocomial RVGE were reported. Results: RVGE proportions were 10.7% (95% CI 5.5% to 18.3%) and 23.8% (95% CI 20.0% to 28.0%) of acute GE ER visits and hospitalisations, respectively; and 21.6% (95% CI 9.8% to 38.2%) of nosocomial acute GE cases. The majority of RVGE cases occurred in children aged <24 months (53%). RV infection peaked between December and May (31.4%). The most common RV genotypes were G4 (59.6%) and P[8] (75.2%). The median duration of RVGE hospitalisation was 4 days (range 1–10 days). Incidence of nosocomial RVGE was 0.3 (95% CI 0.2 to 0.7)/1000 children-years. The median prolongation of hospitalisation due to nosocomial RVGE was 5 days (range 4–7 days). Conclusions: Our analysis report low proportions of RVGE among acute GE cases in Greece which may be attributable to available RV vaccination in Greece. Future impact/effectiveness studies are necessary to confirm this finding. Clinical Trial Registration: NCT00751686.